IMPLEMENTASI KEBIJAKAN PERCEPATAN PENCEGAHAN STUNTING PADA MASA PANDEMI COVID-19 DI KABUPATEN KUDUS - Erlin Friska; Helen Andriani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The government of Kudus is committed to reducing the stunting rate, by issuing the Perbup Kudus No. 53 of 2020 concerning the Acceleration of Stunting Prevention in Kudus Regency. However, the implementation of convergence in Kudus Regency has not run optimally and is coupled with the COVID-19 pandemic which has caused a refocusing of the budget. The purpose of the study was to analyze the implementation of policies to accelerate stunting prevention during the COVID-19 pandemic in Kudus Regency. This study uses a qualitative approach with data collection through in-depth interviews and document review using the Edward III and Van Meter and Van Horn frameworks. The research was conducted in April-May 2022. The results showed that the implementation of the policy had been running but the sensitive nutrition intervention was not maximized, the communication was carried out virtually, the available resources were sufficient, there were policy guidelines that were known and understood by the policy implementers, the coordination was established not yet optimal, the economic and social environment is not sufficiently supportive and the political environment is sufficient to support policy. The implementation of policies to accelerate stunting prevention during the COVID-19 pandemic has not run optimally. Thus, the implementation of convergence still needs to be improved by carrying out activities in a coordinated manner between institutions. Socialization to the community continues to be intensified so that policy objectives can be achieved. There is a need for policy adjustments with the latest Presidential Regulation regarding the acceleration of stunting reduction.